DEIKSIS RUANG DAN WAKTU DALAM FILM FORENSIC MEDICINE SONG CI KARYA HUGUOHAN - Adha, T Kasa Rullah; Ulfah, Nabila (Jurnal Korpus, 2022)
The purpose of the thesis research entitled "Space Deixis and Time Deixis in the Film Forensic Medicine Song ci (法医宋慈 ) by Hu Guohan" is to determine the types of spatial deixis (locative lexemes, demonstrative lexemes, temporal lexemes) and the forms of time deixis (present time deixes). , time deixis, future time deixis relative time deixis) were the most dominant found. In this study the authors analyzed the form and use of deixis. The researcher uses a qualitative descriptive method. The data in this study is the text that becomes a conversational dialogue in the film Forensic Medicine Song ci (法医宋慈 ) by Hu Guohan. Based on the results and discussion, the researcher concludes that space deixis and time deixis in the film Forensic Medicine Song ci (法医宋慈 ) The author of Hu Guohan's work found that the results of the research data contained 71 space deixis and time deixis consisting of 28 forms of space deixis and 43 forms of time deixis. In addition, the theory that the research results uses the theory of Bambang K.P (1984: 1) shows that the use of deixis is related to the context of speech. Deixis has meaning if it is considered and can be known through the context of the speech.